Auditoría tributaria en la Coop. de Transportes Patria, para disminuir el riesgo de determinación del impuesto en el período 2018 - Erika Lisbeth, Montes Silva (2021)
ABSTRACT In this work entitled "TAX AUDIT IN THE COOP. OF TRANSPORTATION PATRIA TO REDUCE THE RISK OF DETERMINING THE TAX IN THE PERIOD 2018, being this a source of evaluation to determine if the financial institution correctly fulfils all the formal duties, at the time of declaring and paying its taxes. The research work is distributed in 5 chapters as follows: Reference framework, theoretical framework, methodological framework, results and discussion, conclusions and recommendations. For the implementation of this audit, the necessary techniques and tools were used to verify that the tax liability will be based on the information provided by the entity, documents, accounting records and statements supporting and supporting the transactions in order to identify any errors or infringements that have been committed during the fiscal period of 2018. Finally, the results were released, where the tax and economic situation of the cooperative Patria of interprovincial transport can be determined, so that based on this the respective conclusions and recommendations can be issued. KEY WORDS: Tax Audit, taxation, infractions, tax penaltie Reviewed by: Danilo Yépez Oviedo English professor UNACH c.c. 0601574692